Recent advances in drug delivery applications of cubosomes, hexosomes, and solid lipid nanoparticles - Anan Yaghmur; Huiling Mu (Elsevier, 2021)
The use of lipid nanocarriers for drug delivery applications is an active research area, and a great interest has particularly been shown in the past two decades. Among different lipid nanocarriers, ISAsomes (Internally self-assembled somes or particles), including cubosomes and hexosomes, and solid lipid nanoparticles (SLNs) have unique structural features, making them attractive as nanocarriers for drug delivery. In this contribution, we focus exclusively on recent advances in formation and characterization of ISAsomes, mainly cubosomes and hexosomes, and their use as versatile nanocarriers for different drug delivery applications. Additionally, the advantages of SLNs and their application in oral and pulmonary drug delivery are discussed with focus on the biological fates of these lipid nanocarriers in vivo. Despite the demonstrated advantages in in vitro and in vivo evaluations including preclinical studies, further investigations on improved understanding of the interactions of these nanoparticles with biological fluids and tissues of the target sites is necessary for efficient designing of drug nanocarriers and exploring potential clinical applications.